Extending Serum Half-life of Albumin by Engineering Neonatal Fc Receptor (FcRn) Binding - Andersen, Jan Terje (American Society for Biochemistry and Molecular Biology, 2014)
A major challenge for the therapeutic use of many peptides and proteins is their short circulatory half-life. Albumin has an extended serum half-life of 3 weeks because of its size and FcRn-mediated recycling that prevents intracellular degradation, properties shared with IgG antibodies. Engineering the strictly pH-dependent IgG-FcRn interaction is known to extend IgG half-life. However, this principle has not been extensively explored for albumin. We have engineered human albumin by introducing single point mutations in the C-terminal end that generated a panel of variants with greatly improved affinities for FcRn. One variant (K573P) with 12-fold improved affinity showed extended serum half-life in normal mice, mice transgenic for human FcRn, and cynomolgus monkeys. Importantly, favorable binding to FcRn was maintained when a single-chain fragment variable antibody was genetically fused to either the N- or the C-terminal end. The engineered albumin variants may be attractive for improving the serum half-life of biopharmaceuticals.